Simultaneous water and vapour transfer in an unsaturated mudstone in badlands terrain, southwestern Taiwan. Issue 13 (25th August 2020) - Higuchi, Kohei; Chigira, Masahiro; Lee, Der‐Her; Wu, Jian‐Hong
Abstract: The simultaneous transfer of pore fluid and vapour was studied in the unsaturated shallow subsurface of a Plio‐Pleistocene marine mudstone badland slope in southwestern Taiwan during the dry season using field monitoring data and numerical simulations. Data from field monitoring show mass‐basis water contents of ~0.05 to ~0.10 that decrease towards the unsaturated ground surface and were invariant during the middle part of the dry season, except for daily fluctuations. In addition, the observed daily fluctuations in water content correlate with fluctuations in bedrock temperature, especially at depths of 2.5–5.0 cm. Periodic increases in water content occurred most notably during the day, when the bedrock temperature showed the greatest increase. Water contents then decreased to the previous state as bedrock temperature decreased during the night. Calculated vapour fluxes within the mudstone during the day increased up to 6 × 10 −6 –1 × 10 −5  kg m −2  s −1, deriving a 0.01–0.02 increase in mass‐basis water content at 2.5 cm depth for a 12‐h period. This agrees with field monitoring data, suggesting that increases in water content occurred due to vapour intrusions into the bedrock. Pore water electrical conductivity (EC) showed periodic variations due to vapour intrusion, and gradually increased between the ground surface and depths of 2.5–5.0 cm. In contrast, pore water EC gradually decreased between 15 and 40 cm depth. Calculated water fluxes at depths of 2.5–40.0 cm varied from −4 × 10 −6 to −2 × 10 −9  kg m −2  s −1 . These fluxes generated an increase in solute concentrations at the ground surface, with negative values of water flux indicating an upwards movement of water towards the surface. We show that the increase in solute content due to solute transfer from depth is highly dependent on variations in water flux with depth. © 2020 John Wiley & Sons, Ltd. Abstract : We calculated hydrological fluxes in the shallow subsurface in the mudstone slope in badlands, southwestern Taiwan, using in‐situ monitoring results of Higuchi and co‐workers. And we revealed flow processes of water and vapour within the unsaturated bedrock during the dry season, which triggered salt concentration near the slope surface and rapid erosion in the subsequent rainy season.